Organometallic Magnets - Chandrasekhar, Vadapalli; Pointillart, Fabrice; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume highlights the recent advances and state of art in the experimental and theoretical studies of organometallic magnets. A plethora of organic ligands such as Mannich-base derivatives, redox-active chromophores, cyanides, Schiff base among others are used to coordinate to 3d transition metals, 4f lanthanides and 5f actinides to design the molecular magnets. Deep analysis of the coordination sphere symmetry, electronic distribution, luminescence are investigated to perform magneto-structural correlation leading to a better understanding of the magnetic properties. Furthermore, the rationalization of the magnetic behavior can be reached using ab initio calculations. The multiple applications that these molecular magnets offer could revolutionize the high-density data storage, spintronics and quantum computing technologies. This volume provides a discussion of these topics from leading international experts and will be a useful reference for researchers working in this field.
Hybrid organic-inorganic cyanide-bridged networks -- Cobalt(II) Complexes as Single-ion Magnets -- Cobalt(II)/(III)-Lanthanide(III) Complexes as Molecular Magnets -- Mannich-base ligands as versatile platforms for SMMs -- Tetrathiafulvalene-based magnets of lanthanides -- Geometry and Magnetism of Lanthanide Compounds -- Single Ion Anisotropy: An Insight to Complicated Magnetic Molecules -- Various groups on cyclopentadienyl-containing molecular magnets -- Ab initio calculations on lanthanide single-molecule magnets -- Analyze the magnetic behavior of metal complexes with organic ligands in terms of ab-initio magnetization densities and the associated orbitals -- Magnetism of Actinide Coordination Compounds.
Keywords: Organometallic chemistry .; Magnetism; Chemistry, Physical and theoretical; Inorganic chemistry; Organometallic Chemistry; Magnetism; Theoretical Chemistry; Inorganic Chemistry